Effects of Dabigatran in Mouse Models of Aging and Cerebral Amyloid Angiopathy - Michael, Neethu; Grigoryan, Mher Mahoney; Kilday, Kelley; Sumbria, Rachita K.; Vasilevko, Vitaly; van Ryn, Joanne; Cribbs, David H.; Paganini-Hill, Annlia; Fisher, Mark J. (Frontiers in Neurology, 2019)
Oral anticoagulants are a critical component of stroke prevention, but carry a risk of brain hemorrhage. These hemorrhagic complications tend to occur in elderly individuals, especially those with predisposing conditions such as cerebral amyloid angiopathy. Clinical evidence suggests that newer oral anticoagulants are safer than traditional oral anticoagulants. We analyzed whether the new anticoagulant dabigatran produces cerebral microhemorrhage (the pathological substrate of MRI-demonstrable cerebral microbleeds) or intracerebral hemorrhage in aged mice with and without hemorrhage-predisposing angiopathy. We studied aged (22 months old) Tg2576 (a model of cerebral amyloid angiopathy) and wild-type (WT) littermate mice. Mice received either dabigatran etexilate (DE) (Tg N=7; WT N=10) or vehicle (Tg N=9; WT N=7) by gavage for four weeks. Anticoagulation effects of DE were confirmed using thrombin time assay. No mice experienced intracerebral hemorrhage. Cerebral microhemorrhage analysis, performed using Prussian-blue and H&E staining, showed no significant change in either number or size of cerebral microhemorrhage in DE-treated animals. Analysis of biochemical parameters for endothelial activation (ICAM-1), blood-brain barrier disruption (IgG, claudin-5, fibrinogen), microglial activation (Iba-1) or astrocyte activation (GFAP) showed neither exacerbation nor protective effects of DE in either Tg2576 or WT mice. Our study provides histological and biochemical evidence that aged mice, with or without predisposing factors for brain hemorrhage, tolerate anticoagulation with dabigatran. The absence of dabigatran-induced intracerebral hemorrhage or increased frequency of acute microhemorrhage may provide some reassurance for its use in high-risk patient populations.